Clinical target volume delineation in glioblastomas: pre-operative versus post-operative/pre-radiotherapy MRI - Farace, P (The British Institute of Radiology., 2011)
OBJECTIVES: Delineation of clinical target volume (CTV) is still controversial in glioblastomas. In order to assess the differences in volume and shape of the radiotherapy target, the use of pre-operative vs post-operative/pre-radiotherapy T(1) and T(2) weighted MRI was compared. METHODS: 4 CTVs were delineated in 24 patients pre-operatively and post-operatively using T(1) contrast-enhanced (T1(PRE)CTV and T1(POST)CTV) and T(2) weighted images (T2(PRE)CTV and T2(POST)CTV). Pre-operative MRI examinations were performed the day before surgery, whereas post-operative examinations were acquired 1 month after surgery and before chemoradiation. A concordance index (CI) was defined as the ratio between the overlapping and composite volumes. RESULTS: The volumes of T1(PRE)CTV and T1(POST)CTV were not statistically different (248 ± 88 vs 254 ± 101), although volume differences >100 cm(3) were observed in 6 out of 24 patients. A marked increase due to tumour progression was shown in three patients. Three patients showed a decrease because of a reduced mass effect. A significant reduction occurred between pre-operative and post-operative T(2) volumes (139 ± 68 vs 78 ± 59). Lack of concordance was observed between T1(PRE)CTV and T1(POST)CTV (CI = 0.67 ± 0.09), T2(PRE)CTV and T2(POST)CTV (CI = 0.39 ± 0.20) and comparing the portion of the T1(PRE)CTV and T1(POST)CTV not covered by that defined on T2(PRE)CTV images (CI = 0.45 ± 0.16 and 0.44 ± 0.17, respectively). CONCLUSION: Using T(2) MRI, huge variations can be observed in peritumoural oedema, which are probably due to steroid treatment. Using T(1) MRI, brain shifts after surgery and possible progressive enhancing lesions produce substantial differences in CTVs. Our data support the use of post-operative/pre-radiotherapy T(1) weighted MRI for planning purposes.